Pariahs or Partners? : Patterns of Government Formation with Radical Right Parties in Central and Eastern Europe, 1990-2020 - Kossack, Oliver 1985- (Edition Politik, 2023)
In the past three decades, radical right parties had the opportunity to directly influence political developments from the highest public office in many post-communist Central and Eastern European countries. Oliver Kossack provides the first comprehensive study on government formation with radical right parties in this region. Even after the turn of the millennium, some distinct features of the post-communist context persist, such as coalitions between radical right and centre-left parties. In addition to original empirical insights, the time-sensitive approach of this study also advances the discussion about concepts and methodological approaches within the discipline